Pengembangan Aplikasi Mobile Pemesanan Katering Sekolah Berbasis Platform Android - Ardhan Maulana Zuhdi; Herman Tolle; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The implementation of the full-day school concept is currently around 8,000 schools throughout Indonesia. In the implementation, student's activities during school are held for 8 hours per day. Some of the students get a pocket money to buy food in the cafeteria because their parents do not have time to cook the lunch for brunch and some their busy parents entrust the catering service to fulfill their child's nutrition but The majority all students who subscribed to catering leave their lunch and some do not eat all food on the reason because menu in catering is not liked by the students. This causes students to eventually lack calories to fulfill the activities on that day. These problems will also affect the concentration and learning achievement of students. Based on the above problems it takes innovation in the school catering ordering service that provides innovations in school catering ordering and provides children nutrition supervision for parents who subscribe to catering. The development of school catering ordering applications is developed to help parents supervise the nutrients on each menu in the catering package to suit the needs of each child. Based on the usability test, the value of 87,125% results that indicates the catering booking app is eligible to be used and applied. In the test, functionality shows that the system is valid and worth using for school catering reservations.